The implementation of a new pop cosmopolitanism concept in the process of mediatization of Japanese mass culture - Pashchenko, Bogdan; Kyrylova, Oksana; Pavlenko, Victoriia; Blynova, Neliia (Journal of Print and Media Technology Research, 2021)
This academic work deals with a concept of a new pop cosmopolitanism presented by Henry Jenkins and scrutinizes the ways it implements in the process of mediatization of Japanese mass culture. The paper highlights a local and comprehensive pop cosmopolitanism as characteristics of recipients of Japanese mass culture, e.g. anime, manga and games. Mediatization of Japanese mass culture provides a cultural convergence, when people perceive parts of foreign culture as their own, and become the cosmopolites. In addition, other countries start using the elements of Japanese mass culture to fulfill the needs of its own and the Western audiences, for instance Chinese game company develops a game in Japanese anime style to sell it to the West. We analyze the spreading of Japanese mass culture in two directions: channels of spreading and techniques of entering the global level. Our research represents the manifestations of a new pop cosmopolitanism on examples of games, online anime-styled characters, e.g. vocaloids and virtual youtubers, anime and manga franchises and anime streaming services. This piece of work aims to show how mediatization makes Japanese language a brand in terms of cosmopolitanism and cultural exchange. The paper is of current importance due to a broad spread of diverse elements of Japanese mass culture around the world and steady rise of its popularity within people of all nationalities. The results of the research can be useful for further explorations of Japanese and international media discourse.